Ozone concentration profile retrieval from ground-based high-resolution thermal infrared spectra. - Van Delst, Paul F. (Curtin University, 1996)
Simulations of the Atmospheric Emitted Radiance Interferometer (AERI), a ground-based, high-resolution infrared detection system, are used to produce retrieved atmospheric ozone concentration profiles. A line-by-line transmittance model, FASCD3P, is used for the forward model and a maximum likelihood retrieval scheme is employed for the inverse model. An a priori data set consisting of 83 midlatitude winter ozone sondes is used to condition the inversion. Three iterations are required to reduce the radiance residuals to less than the instrument noise. The retrieval accuracy below 300mb is within 25% of truth. Above 300mb, variance within the a priori data is the dominant source of retrieval error. This is due to the number of retrieved layers (27) being higher than the amount of independent information present in the radiance spectra (approximately 4) so much of the retrieval information above 300mb comes from the a priori data.